Dengue Vaccines: Current Status and Future Perspectives - Vasantha Kamath; A. B. Aishwarya (Wolters Kluwer Medknow Publications, 2024)
Dengue fever (DF), caused by the dengue virus (DENV), is a major public health problem worldwide, with approximately 390 million reported annual infections. The lack of specific antiviral therapies and limited means of vector control has led to the development of a dengue vaccine as a promising strategy to combat this disease. The purpose of this review is to provide a comprehensive analysis of the current status and prospects of dengue vaccines. This review describes different approaches used in dengue vaccine development, including live-attenuated, inactivated, subunit, and viral vector vaccines. Each approach is evaluated for immunogenicity, safety, and efficacy based on preclinical and clinical studies, highlighting the strengths and limitations of each vaccine candidate. Future directions and research priorities in dengue vaccine development are highlighted. In conclusion, dengue vaccines have great potential to reduce the burden of DF worldwide. However, some challenges remain regarding vaccine safety, efficacy, delivery, and availability. By addressing these challenges and leveraging advances in vaccine technology, there can be more effective control and prevention of DF and protection of public health, leading to improvement in the quality of life.